ANIMISME DALAM PEMUJAAN BARONG BULU GAGAK DI BALI - I Putu Ariyasa Darmawan (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2020)
Barong as a tool of worshiping God had an animating power which functions as a protector and unifier of the community. The six of Barong crow feathers that found in Bali had a bond in terms of feather source namely Alas Arum Temple which located at Alas Baha, Mengwi District, as a place to beg crow feather. Barong Crow Feather also united by the kinship among Barong Crow Feather, such as the birth relation and visited each other in the ceremony. The animates power of Barong Crow Feather in Bali is believed to protect the community, bound the social religious, provided the serenity, and increased the belief to the almighty God in the form of Barong. In the essence, the society did not worship the Barong form, but the power which animated a facility because the limitation of human ability in imaging and worship the Almighty God.